ANALISIS PERSEPSI DAN PENDAPATAN PETANI PESERTA ASURANSI USAHATANI PADI (AUTP) DI KECAMATAN BRATI KABUPATEN GROBOGAN - administrator, administrator; Safitri, Ertiana; Budiraharjo, Kustopo; Roessali, Wiludjeng (Fakultas Pertanian Universitas Wijaya Putra, 2023)
Climatic conditions that often change and are difficult to predict have a negative impact on natural disasters such as floods, droughts and increasing pest attacks that affect crop damage. Efforts to minimize this by participating in the rice farming business insurance program. Farmers' participation in the AUTP program is still low, therefore it is necessary to know the perception of farmers towards AUTP. Production inputs used by farmers are not optimal, which can result in non-optimal production yields and farmer income. The purpose of this study is to analyze farmers' perceptions of AUTP, rice farming income with Grobogan MSE, factors that affect the income of AUTP farmers. This study was conducted in Lemah Putih Village with a sample of 60 farmers from a population of 105 farmers. Determination of the number of samples taken using the Slovin method where respondents were taken proportionally sampling. Data analysis method with likert scale, multiple linear regression, one sample t test. The results of the research on farmers' perceptions of the AUTP program are overall in the good category. The perception of farmers in terms of socialization is not good, participant registration is very good, premiums are good, claims and benefits are not good. Rice farming is profitable compared to Grobogan MSE. The cost of seeds, labor, farm experience has a significant effect on income. Fertilizer costs, selling prices of rice have no real effect on income